2019
DOI: 10.24251/hicss.2019.709
|View full text |Cite
|
Sign up to set email alerts
|

Understanding User Uncertainty during the Implementation of Self-Service Business Intelligence: A Thematic Analysis

Abstract: Owing to Self-Service Business Intelligence (SSBI) systems' transformative power for organizations, substantial user uncertainties often blight their potential. Although these uncertainties pose a significant threat to effective SSBI implementation, their sources and determinants remain unclear. We conducted semi-structured interviews with 15 current users of a recently implemented SSBI system to empirically explore the relevant factors of user uncertainty. We undertook a rigorous thematic analysis of the coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…One important factor which affects the SSBI environment is the staff training. Weiler et al (2019) argue that there are no standardized training programs for SSBI. This is also supported by the experts, which is presented in the empirical findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One important factor which affects the SSBI environment is the staff training. Weiler et al (2019) argue that there are no standardized training programs for SSBI. This is also supported by the experts, which is presented in the empirical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Flexibility Difficult to scale Software architecture Data governance and integration. (Imhoff & White, 2011) Saves resources (Lennerholt , et al, 2018) User uncertainty (Weiler , et al, 2019) Facilitates the access data Access of source data to business users (Alpar & Schulz, 2016) Improves decision making, agility and Business users lack the needed skills when efficiency (Schlesinger & Rahman, 2015; using SSBI tools. (Johannessen & Fuglseth, Lizotte-Latendresse & Beauregard, 2018;) Alpar & Schulz, 2016 Less dependency on the IT department Implementation challenges (Lennerholt , et al, (Alpar & Schulz, 2016) 2018)…”
Section: Advantages Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eckerson [17] argues that implementing SSBA is more complex than it looks. Research by Weiler et al [21] has shown that user uncertainty also has a negative impact on the introduction of SSBA. The reasons for uncertainty can be due to 'hard factors' (e.g., a lack of technical skills and capabilities) and by 'soft factors' (social dynamics, fear of AI and non-transparency).…”
Section: Self-service Business Analytics (Ssba)mentioning
confidence: 99%
“…For example, authors have attempted to describe SSBA architecture to promote more understanding of what SSBA is from a technical perspective [6]. Others have explored the factors influencing SSBA acceptance [7], user uncertainty during engagement [8] and the gap it creates between a user and an IT department [9]. When it comes to the benefit of SSBA, empirical evidence suggests that SSBA enables organizational agility [5] and employees communication and collaboration [10].…”
Section: Introductionmentioning
confidence: 99%